Biological importance of bioactive phytochemical 'Cimifugin' as potential active pharmaceutical ingredients against human disorders: A natural phytochemical for new therapeutic alternatives - Dinesh Kumar Patel (Elsevier, 2023)
Backgrounds: Herbal medicines have been used in medicine against numerous kinds of human disorders and associated secondary complications since a very early age. Herbal medicines have huge biological potential in medicine mainly due to its therapeutic potential and fewer side effects. Herbal medicines have been composed with plant and their derived pure phytochemicals. Coumarins are oxygenated heterocyclic class phytochemical, found to be present in the plants, bacteria and fungi. Coumarins were present in the Ferulago campestris, Murraya paniculata, Aegle marmelos and tonka beans. Cimifugin is an important coumarin class phytochemical of Saposhnikovia divaricata and Cimicifuga racemosa. Methods: Scientific data of medicinal importance, pharmacological activities and analytical aspects of cimifugin have been collected from Science Direct, PubMed, Google Scholar, Scopus and Google and analyzed in the present work in order to know the therapeutic potential of cimifugin. The biological importance of furanocoumarins and coumarins has also been discussed in the present work in order to understand the biological importance of cimifugin. Pharmacological activities of cimifugin with different therapeutic targets have been investigated in the present work. However, analytical techniques for the determination of cimifugin in different samples were also discussed in the present work. Results: Biological importance of cimifugin in medicine for treatment of different types of human disorders and associated complications has been discussed in the present work. Cimifugin have biological effects on hepatic disorders, bone disease, allergic reaction, inflammatory disorders, psoriasis, cancer, and neurodegenerative diseases. Further, its molecular mechanisms underlying their curative effects were also presented. Analytical developments for the determination of cimifugin in different biological samples have also been presented in this work. Conclusion: Cimifugin will be used in medicine for the treatment of human disorders and associated secondary complications in the future.